Business process outsourcing and offshoring : could Yahluma compete? - Metton, Eulalie; Mosala, Thabo ([London] : SAGE, 2016)
In January 2009, young entrepreneurs Ayanda Qunu and Thembi Bhayi abandoned their plans to start a fully owned contact centre, Yahluma Solutions Ltd, in Buffalo City in the Eastern Cape, South Africa. Even with the assistance of a financial incentive from the Department of Trade and Industry (DTI) to encourage the establishment of business process outsourcing and offshoring (BPO&O) businesses, they asked themselves: could they have competed globally and locally? Was their decision to abandon their plans correct?
Originally Published in: Metton, E., & Mosala, T. (2013). Business Process Outsourcing and Offshoring: Could Yahluma Compete? WBS-2013-19. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Contracting out -- Case studies; Business failures -- Case studies